HUBUNGAN ANTARA PERSALINAN SECARA SECTIO CAESAREA DENGAN KEJADIAN ASFIKSIA NEONATORUM DI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO TAHUN 2009 - Maya Safitri (Viva Medika, 2009)
Mother mortality in Indonesia in 2007 th yet is high, that’s equal to 228/100.000 birth of life. WHO approximating about 10% birth of life experiencing of complication haemorrahage childbirth pasca. Pasca caesarea sectio infection also represent important cause of and death painfulness of mother. In RSUD Prof. dr. Margono Soekardjo Purwokerto occurence of caesarea sectio more compared to RSUD Banyumas that is 5.250 case or about 38,6% from 13,569 amount of childbirth. Objective : To know relation between childbirth by sectio caesarea with occurence of neonatorum asphyxia in RSUD Prof. dr. Margono Soekardjo2009 th . This research use analytic survey with approach of retrospektif, using sekunder data from RSUD Prof. dr. Margono Soekardjo Purwokerto 2009 th . Bivariate analysis with Chi Square data analysis. Amount of sampel counted 98 mother childbirth.Percentage of is biggest of occurence of neonatorum asphyxia happened at sampel with childbirth by sectio caesarea counted 45 sampel (70,3%). With p-value is 0,005 with signifikan level 10% ( 0,1). So that p-value < 10% ( 0,005 < 0,1) or x 2 count > x 2 of is tables of ( 7,867 > 3,841) then Ho refused and Ha accepted. Childbirth by sectio caesarea relate to occurence of neonatorum asphyxia. Keyword : Sectio Caesarea, Asphyxia Neonatorum.